2014
DOI: 10.1136/bmjspcare-2014-000654.123
|View full text |Cite
|
Sign up to set email alerts
|

Hospice at Home: Optimising Care and Enabling Home Death

Abstract: BackgroundThe Cambridgeshire Hospice at Home (H@H) service provides specialist community care for people approaching the end of their lives, enabling them to be cared for and to die at home if that is their wish. An independent evaluation is underway that is both shaping the evolving service and providing commissioners with detailed information needed to ensure continuing NHS funding.MethodsA multifaceted approach has employed:a) Detailed case-note review of all 450 patients referred to the service between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…25 GPs were important in enabling access to the service, if they deemed that a patient could be cared for at home, 39 and if a family required psychological support and needed practical help for symptom control. 35,36 Referrals were also being appropriately triaged by the senior nurse at the hospice at home service using a RAG rating on the severity of clinical need of the patient and family. In terms of monitoring the criteria for service admission, the main tool used for reporting was whether patients died in their preferred place.…”
Section: "Sustainable Funding Model"mentioning
confidence: 99%
See 2 more Smart Citations
“…25 GPs were important in enabling access to the service, if they deemed that a patient could be cared for at home, 39 and if a family required psychological support and needed practical help for symptom control. 35,36 Referrals were also being appropriately triaged by the senior nurse at the hospice at home service using a RAG rating on the severity of clinical need of the patient and family. In terms of monitoring the criteria for service admission, the main tool used for reporting was whether patients died in their preferred place.…”
Section: "Sustainable Funding Model"mentioning
confidence: 99%
“…In terms of monitoring the criteria for service admission, the main tool used for reporting was whether patients died in their preferred place. 35 "Knowledge and Skills of Care Providers"…”
Section: "Sustainable Funding Model"mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Rationale for parental preference for home death include families feeling more supported at home, with less disruptions and more normalcy. 17 Multiple studies have shown improved psychological functioning and adjustment in parents whose child died at home. 14 Parents also perceive improvement in their child's quality of life and happiness at home.…”
Section: Pediatric Death In the United Statesmentioning
confidence: 99%
“…16 These data parallel findings in adults (and their families) with similar chronic conditions who also prefer home death if feasible. 17 Multiple studies have shown improved psychological functioning and adjustment in parents whose child died at home. 14,18,19 A study of parents whose children had died either at home or in the hospital of a cancer diagnosis showed significantly higher depression ratings in parents of hospital deaths.…”
Section: Pediatric Death In the United Statesmentioning
confidence: 99%